The Influence of Budgeting System, Organizational Culture, and Firm Size to Performance - Mochamad Muslih (President University, 2018)
There are inconsistencies in past research results regarding the impact of budgets on performance. Some studies concluded that budgeting process had significant effect on performance, but some studies didn’t. The purpose of this study is to determine the influence of budgeting system on performance.This research used quantitative research method. Organizational culture and firm size are added as control variables. The population of this research are companies listed at Bursa Efek Indonesia classified as LQ45. The samples of research are companies classified as LQ45 taken randomly.The results showed the budgeting process has significant effect on firm performance but with different sign. It means that budgeting process gives negative effect to firm performance. Organizational culture and firm size have significant positive effect on firm performance.